Enhancing Student Interactions in Online Learning: A Case of Using YouTube in a Distance Learning Module in a Higher Education Institution in Uganda - Namubiru Ssentamu, Proscovia; Ngambi, Dick; Bagarukayo, Emily; Baguma, Rehema; Mutambo Nabushawo, Harriet; Nalubowa, Christine (Higher Education Research, 2020)
One of the challenges facing higher education institutions in general and Uganda in particular, is the widening gulf between increased use of technology for teaching and learning and achieving meaningful learning outcomes, especially in the face of the COVID-19 pandemic. In this paper, we report on one use of technology where a teacher’s integration of YouTube videos in teaching increased students’ levels of interaction with the content of the video, with peers and with the instructor (teacher). Guided by the sequential mixed-method design, a series of online learning activities were designed and matched with a carefully selected YouTube video. The activity was piloted and refined for use on purposefully selected teaching staff. The staff watched the videos that were uploaded on the Virtual Learning Environment (VLE) and responded to online learning tasks at individual and group levels. The VLE served as a knowledge sharing space for reflections. The paper concludes that lesson design was critical in enriching the VLE with carefully selected YouTube videos. Our key recommendations are: focus on the learning outcomes, design for the desired interactions, build into the task reflections, and decide whether to pre-select YouTube videos for students or to allow students to find appropriate YouTube videos; use reflections and knowledge sharing spaces. Further work has built reflective questions in the video which allows student to pause and reflect.
Keywords: Digital Taxonomy; Distance Learning; Higher Education; Interactive Learning; Student Pedagogical Support; Virtual Learning Environment; YouTube